2012
DOI: 10.1088/1468-6996/13/5/055002
|View full text |Cite
|
Sign up to set email alerts
|

Electrical isolation of dislocations in Ge layers on Si(001) substrates through CMOS-compatible suspended structures

Abstract: Suspended crystalline Ge semiconductor structures are created on a Si(001) substrate by a combination of epitaxial growth and simple patterning from the front surface using anisotropic underetching. Geometric definition of the surface Ge layer gives access to a range of crystalline planes that have different etch resistance. The structures are aligned to avoid etch-resistive planes in making the suspended regions and to take advantage of these planes to retain the underlying Si to support the structures. The t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
14
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 39 publications
1
14
0
Order By: Relevance
“…3 Â 10 9 cm À2 from the straight through condition. The TDD is identical for the frame and suspended Ge; however, the misfit dislocation network that is observed at the Si/Ge interface largely disappears when the Si substrate is removed, confirming our previous speculation 29 that the misfit network is removed on etching. Hence, the crystalline quality at the bottom interface of the Ge layer is improved and so is electrical isolation by eliminating surface to surface conduction through dislocations.…”
Section: Plan View Tem and Afmsupporting
confidence: 84%
See 2 more Smart Citations
“…3 Â 10 9 cm À2 from the straight through condition. The TDD is identical for the frame and suspended Ge; however, the misfit dislocation network that is observed at the Si/Ge interface largely disappears when the Si substrate is removed, confirming our previous speculation 29 that the misfit network is removed on etching. Hence, the crystalline quality at the bottom interface of the Ge layer is improved and so is electrical isolation by eliminating surface to surface conduction through dislocations.…”
Section: Plan View Tem and Afmsupporting
confidence: 84%
“…As an example, Figure 1(a) shows a compressively strained Ge 23 layer grown epitaxially on Si via a strain tuning buffer 24,25 with the aim of improving hole mobility, however, the large dislocation density in the top-most strained layer means that leakage by dislocation conduction could be an issue. [26][27][28] We showed previously 29 that electrical isolation in such a Ge-on-Si structure can be improved by suspending the Ge layer, interpreting this as being due to removing the conduction path through the network of misfit dislocations (Figure 1(b)). In this report, we present further evidence that these misfits are indeed removed.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[10][11][12] Generally, research efforts have focused on reducing the threading dislocation density (TDD); however, it has been speculated that the deleterious surface-to-surface conduction could be prevented if instead the misfit dislocations could be removed. 13 A possible approach to achieve this is by suspending the Ge layer, which would remove the Ge/Si interface and potentially the majority of the misfit dislocation network. In this way, tensile strained Ge membranes could be enabled for use as platforms for complimentary metal-oxidesemiconductor (CMOS), optoelectronic and cryogenic integration purposes.…”
mentioning
confidence: 99%
“…However, under sufficient tensile strain Ge can becoming a direct band gap material and so a tensile-strained Ge crystalline membrane could be a useful platform for a Ge light source, or other Ge-based optical devices. Recently, thin (<1 lm) freestanding Ge membranes 22,23 and various other suspended structures 13 have been fabricated through relatively simple processing. Nam et al 22 and Kurdi et al is not homogenous in its properties then other effects apparently observed on further straining may be a composite from a spectrum of different strain values and in actuality luminescence may be shaper, rather than broader, in response to strain.…”
mentioning
confidence: 99%